Pentingnya Kepemimpinan dalam Kesuksesan Bisnis Kewirausahaan - Hepni Putri; Presi Nila Sari; Yosia Belo (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Leadership plays a very important role in determining the success of an entrepreneurial business. Not only focusing on making the right decisions, a leader is also required to create an environment that supports innovation, build a solid team, and be able to manage the uncertainty that arises in the dynamics of the business world. An effective leader can provide a clear vision, inspire the team, and develop a positive and productive company culture. The ability to adapt to market and technological changes and make wise decisions are also key factors in achieving long-term goals. Therefore, strong leadership can optimize team potential, increase motivation, and ensure the continuity and growth of a sustainable business.